Prevalence and correlates of sexual dysfunction among patients with mental disorders in a tertiary hospital in Southwest Nigeria (2021)
Background: Sexual dysfunction is more common among patients with mental disorders compared to the general population. Despite this high occurrence, information regarding sexual dysfunction as well as their correlates in patients receiving care for mental disorders in developing countries is still sparse. Aim: To determine the prevalence and correlates of sexual dysfunction among patients with mental disorders receiving care in a tertiary hospital in Southwest Nigeria. Setting: This study was performed at the psychiatric outpatient clinic at the University College Hospital, Ibadan, Southwest Nigeria. Methods: A cross-sectional study was conducted on a convenience sample of 238 adults aged 18–60 years. Socio-demographic and clinical information was obtained from all recruited patients. Sexual dysfunction was assessed using the International Index of Erectile Function questionnaire for men and the Female Sexual Function Index questionnaire for women. Questionnaires for measuring depression, medication adherence and autonomic medication side effects were also administered. Associations between sexual dysfunction and socio-demographic and clinical factors were explored. Results: The prevalence rates of sexual dysfunction among male and female participants were 84.7% and 95.7%, respectively. In the multivariate analysis, employment status and autonomic side effects of psychotropic medications significantly predicted male sexual dysfunction, while religion and employment status were predictors of female sexual dysfunction. Conclusion: Sexual dysfunction is very common among patients with mental disorders, with higher rates in female participants. There is a need for clinicians to consider routine screening for sexual dysfunction in psychiatric outpatients with a view of providing psychosocial interventions to improve patient’s quality of life.